Associations of low-density lipoprotein cholesterol and hemoglobin A1C with cardiovascular events and mortality in breast and prostate cancer patients - Yen-Chou Chen; Jhih-Yuan Lu; Chun-Yao Huang; Yu-Hsuan Joni Shao (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Cardiovascular disease is a major non-cancer cause of morbidity in cancer patients. Low-density lipoprotein cholesterol (LDL) and hemoglobin A1C (HbA1C) are shared risk factors for cancer and cardiovascular disease. However, optimal management for these factors in cancer patients remains unclear. Methods: This retrospective cohort study investigated associations between LDL and HbA1C levels with major cardiovascular events, all-cause mortality, and cancer recurrence in patients with breast and prostate cancer. The analysis included 832 breast cancer and 593 prostate cancer patients from the Taipei Medical University Clinical Research Database (2011–2020), using Cox proportional hazard models with time-dependent covariates. The findings were validated using the TriNetX research network, using a propensity score matching method. Results: Elevated LDL levels (≥130 mg/dL) were associated with a higher risk of major cardiovascular events, particularly in prostate cancer patients. A U-shaped association was observed between LDL levels and all-cause mortality, with the lowest risk in the 100–129 mg/dL range (propensity score matching risk ratios for all-cause mortality with LDL ≥130 mg/dL: 1.05 [95 % confidence interval 1.02–1.09] for breast cancer and 1.08 [95 % confidence interval 1.04–1.12] for prostate cancer). Elevated levels of HbA1C (≥6 %) were also associated with increased risks of cardiovascular events, with a potential U-shaped association with mortality. Conclusion: Higher levels of LDL and HbA1C are associated with increased risks of cardiovascular events and all-cause mortality in breast and prostate cancer patients, supporting current cardio-oncologic guidelines in cancer survivors.